Validation of the efficacy of the prognostic factor score in the Japanese severity criteria for severe acute pancreatitis: A large multicenter study. Issue 3 (April 2017) - Ikeura, Tsukasa; Horibe, Masayasu; Sanui, Masamitsu; Sasaki, Mitsuhito; Kuwagata, Yasuyuki; Nishi, Kenichiro; Kariya, Shuji; Sawano, Hirotaka; Goto, Takashi; Hamada, Tsuyoshi; Oda, Takuya; Yasuda, Hideto; et al.
Background: The Japanese severity criteria for acute pancreatitis (AP), which consist of a prognostic factor score and contrast-enhanced computed tomography grade, have been widely used in Japan. Objective: This large multicenter retrospective study was conducted to validate the predictive value of the prognostic factor score for mortality and complications in severe AP patients in comparison to the Acute Physiology and Chronic Health Evaluation II (APACHE II) score. Methods: Data of 1159 patients diagnosed with severe AP according to the Japanese severity criteria for AP were retrospectively collected in 44 institutions. Results: The area under the curve (AUC) for the receiver-operating characteristic curve of the prognostic factor score for predicting mortality was 0.78 (95% confidence interval (CI), 0.74–0.82), whereas the AUC for the APACHE II score was 0.80 (95% CI, 0.76–0.83), respectively. There were no significant differences in the AUC for predicting mortality between two scoring systems. The AUCs of the prognostic factor scores for predicting the need for mechanical ventilation, the development of pancreatic infection, and severe AP according to the revised Atlanta classification were 0.84 (95% CI, 0.81–0.86), 0.73 (95% CI, 0.69–0.77), and 0.83 (95% CI, 0.81–0.86), respectively, which were significantly greater than the AUCs for the APACHE II score; 0.81 (95% CI, 0.78–0.83) for the need for mechanical ventilation ( p  = 0.03), 0.68 (95% CI, 0.63–0.72) for the development of pancreatic infection ( p  = 0.02), and 0.80 (95% CI, 0.77–0.82) for severe AP according to the revised Atlanta classification ( p  = 0.01). Conclusion: The prognostic factor score has an equivalent ability for predicting mortality compared with the APACHE II score. Regarding the ability for predicting the development of severe complications during the clinical course of AP, the prognostic factor score may be superior to the APACHE II score.